Improved Wettability and Dimensional Stability of Bamboo Timber by Coating Graphene/Silica Composites - Jin Wang; Ye Zhou; Jingpeng Li; Yongshun Feng; Jian Zhang; Haixia Yu; Xiaowei Zhuang (International Journal of Polymer Science)
Bamboo timber (BT) is a kind of natural porous material, and usually bamboo cracking and deformation are caused by the change of humidity in the environment. Inspired by the natural structure of the shell, a multilayer structure was designed to fabricate a kind of graphene/silica composite coating on the BT surface. The multilayer bamboo composite (FAS-RGO@SiO2BT) was prepared by using the self-assembly process of nanospherical silica on graphene followed by hydrophobic modification. A possible formation mechanism of FAS-RGO@SiO2BT was discussed by X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray analysis, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy. The FAS-RGO@SiO2BT has excellent hydrophobic properties for tea, orange juice, milk, coffee, blue ink, red wine, and green juice. Also, the FAS-RGO@ SiO2BT has an obvious hydrophobic effect on any of the various solutions with a pH of 1 to 14. In addition, after a 90-day immersion test, the water absorption rate of FAS-RGO@ SiO2BT is 9.7% and the thickness swelling rate is 0.5%. The wettability and dimensional stability of the FAS-RGO@SiO2BT are significantly improved compared to those of BT.